Microeconomic theory; a mathematical approach - Henderson, M. James; Richard, Quandt E. (Singapore McGraw-Hill book Co, 1980)
This book is a handy reference material in microeconomics especially with a mathematical approach.
Includes index and exercises with answer
ijb, 12/07/2018
Loans
Keywords: Economics, Mathemathical; Microeconomics